Future‐Proofing Institutional Research Skills in an Evolving Digital Institution. Issue 178 (23rd November 2018) - Johnson, Gina; Simon, Jason
Abstract: This chapter utilizes the duties and functions of institutional research to outline the skills needed by institutional research professionals in an evolving digital institution. The concept of future‐proofing, explained and considered in this context, encourages professionals to develop skills for the present with the future needs of data‐informed decision‐making in higher education in mind.